COOPERATIVISMO E CREDITO RURAL DA AGRICULTURA FAMILIAR COMO FOMENTO AO DESENVOLVIMENTO SUSTENTÁVEL: ESTUDO EM UMA COOPERATIVA DE INTERAÇÃO SOLIDÁRIA / Cooperativism and rural credit of family agriculture as a promotion to sustainable development: study in a solidary interaction cooperative - Büttenbender, Pedro Luís; Berkmann, Bruno Alexandre; Sparemberger, Ariosto (Informe GEPEC, 2022)
Este estudo, orientado a partir da Agenda 2030 da ONU, teve por objetivo mensurar a participação da cooperativa de crédito de interação solidária na operacionalização de recursos do PRONAF, contratados por agricultores familiares do Município de São Martinho/RS, no período de 2015 a 2019. A pesquisa foi exploratória, descritiva, de campo e estudo de caso teve uma abordagem quali-quantitativa. Os dados secundários com base em dados bibliográficos e documentais, e primários com dados da cooperativa, entrevistas com lideranças e observação direta. Com uma destacada presença de cooperativas, o município possui sua principal base econômica e social relacionada a agricultura familiar. O crédito rural para agricultura familiar joga um papel decisivo no estímulo à produção, geração de trabalho e renda, inclusão e promoção do desenvolvimento sustentável. Com crescente participação cooperativa, é possível entender melhor a importância do crédito, a qualificação das políticas públicas e a importância das ações cooperativas. ABSTRACT: This study, based on the UN 2030 Agenda, aimed to measure the participation of the credit cooperative’s solidary interaction in the operationalization of PRONAF resources, hired by family farming in the municipality of São Martinho/RS, in Brazil, in the period from 2015 to 2019. The research can be characterized as exploratory, descriptive, field and case study, conducted over a qualitative and quantitative approach. Secondary data was based on bibliographic and documentary data, and primary data was collected from the cooperative through interviews with leaders and direct observation. With a prominent presence of cooperatives, the municipality has its main economic and social base related to family farming. Rural credit for family farming plays a decisive role in stimulating production, generating jobs and income, including and promoting sustainable development. With the increase of cooperative participation, it is possible to better understand the importance of credit, the qualification of public policies and the importance of cooperative actions.